The Effects of Different Cooling Rate Conditions on the Thermal Profile and Microstructure of Al-Si Alloy with Magnesium Addition - Muhammad Faez, Mohamad Tajudin; Asnul Hadi, Ahmad; Juliawati, Alias; Nur Azhani, Abd Razak; Nasrul Azuan, Alang (AIP Publishing, 2024)
Thermal analysis is a technique that has played an important role in the characterization and development of the material. The aim of this study is to investigate the effect of magnesium addition on the cooling rate of an Al-Si alloy with magnesium addition using the method CCA-CA. In this work, a graphite crucible containing Al-Si alloy with an addition of 1% magnesium and up to the temperature of 800 °C was heated using induction furnace. The cooling curve was determined by K-type thermocouples. One K-type thermocouple was placed in the centre of the crucible and the other near the wall of the crucible. Both K-type thermocouples were submerged to 20 mm in the melt. The crucible was left in a chamber with a Kaowool insulator and in an open environment with additional minimal ventilation to achieve the slow and rapid cooling rate condition. The slow and fast cooling rates were calculated at 0.17 °C/s and 1.578 °C/s respectively. The temperature of liquids and solidus of the slow cooling rate condition was found at 579 °C and 464 °C respectively. Meanwhile, the liquidus and solidus temperature of fast cooling rate was at 577 °C and 477 °C. Furthermore, the microstructure formation of different cooling rate conditions were observed. The results show that the increased cooling rate condition refined the grain structure, enhance the grain globularity and reduced the aspect ratio.